EMPLOYEE PERFORMANCE ASSESSMENT IN IMPROVING BUSINESS ACCORDING TO ISLAMIC ECONOMIC PRINCIPLES (Case Study: La Tansa Gontor Department Store) - 'Imari, Iqbal; Susilo, Adib; Fayyidul Haq, Azriel Muhammad (EKOBIS SYARIAH, 2024)
The evolution of Islam has contributed significantly to various areas of human life. Work in the Islamic perspective is one of the necessities of life and an activity that holds an important role in social life. Work is advocated by Islam, and work is frequently used as a measurement to determine a person's worth.The assessment of employee performance is an imperative aspect in improving organizational performance. This study aims to explore the practice of employee performance assessment in improving the business of CV. La Tansa Gontor Department Store by considering the principles of Islamic economics. This research method used is qualitative with a case study at La Tansa Gontor Department Store.This research concludes that employees' performance evaluation conducted by CV. La Tansa Gontor Department Store has implemented the principles of Islamic economics, hence improving employee motivation and overall performance. The practical implication of this research is that the use of a performance evaluation approach based on Islamic economic principles can be a relevant and effective model for other companies seeking an adoption of Islamic values in their business practices